Sistema administrativo y su incidencia en la operatividad de la empresa EMAPAVIN E.P., Vinces, periodo 2014-2015. - Briones Bajaña, Miguel Ángel (2016)
The present investigation carries out the analysis and evaluation of the performance of the administrative system and as it affects in the operability of the company EMAPAVIN E.P., of Vinces in the period 2014 - 2015, through conventional methods like interviews, surveys and censuses. These methods were applied and analyzed to determine the problems encountered in the whole process investigated, since with these instruments it was possible to define in a concise way all the results for the final analysis, corresponding to the applicable suggestions. In the first chapter is the contextual framework of research where the whole problem of research is developed, the second chapter comprises theoretical and conceptual, the third chapter details the methodology of research, the fourth chapter shows the results obtained And the fifth chapter shows the conclusions and recommendations. As an initial step, an interview is conducted with the administrator, to know in detail the current situation in the administrative and operational departments of the company EMAPAVIN EP, as a second step a census is carried out to all the officials who work in the different areas of the Company and to finish the investigation a survey is developed to the users of the locality to determine the level of attention and current satisfaction for the delivery of the potable water service. The results obtained are of great importance for the company EMAPAVIN E.P., to improve the low quality evidenced in both administrative and operational services currently provided to Vinces users. The conclusions that are detailed in the end after thoroughly analyzing all the results give us a clear idea of the real problem that was found in the research carried out in the company of potable water EMAPAVIN EP, this leads to make the respective recommendations being this the Most important point in the development, since they are the ones that show us all the possible applicable solutions to solve all the problems encountered.